Conceptual Interpretation Of Aesthetic Evaluation Standards In Linguistics - Marufova Zulfiya (Genius Publishing Group, 2022)
The article deals with the research of the concept "beauty" by world linguists, Eastern and Western standards of female beauty, their differences and common aspects. The role of universal semes included in the lexico-semantic composition of the concept and their role in the formation of general cultural evaluative standards are also analyzed
Keywords: Beauty; concept; standard; norm